The Influence of Motivation, Communication and The Work Environment on Employee Performance at PT Samudera Raya Berjaya - Deni Faisal Mirza; Lidya Rosa; Harta Louis Pantun; Stevanny; Vincent Leonardo Tannu Wijaya (Journal of Research in Business, Economics, and Education, 2020)
The purpose of this study is to analyze the decline in employee performance at PT Samudera Raya Berjaya. HR plays an important role in achieving the goals of an organization or company. Therefore, human resources are required to be professional and efficient in facing the challenges and opportunities that exist. In this case the organization or company must pay attention to the motivation, communication and work environment of each employee. Motivation shows the encouragement or enthusiasm given by superiors to support employee performance. In addition, communication must be good and good between fellow employees and superiors so that they can get good performance and finally, a bad work environment can also affect employee discomfort in working so that causing decreased employee performance. The validity test is used with a population of 100 people and 30 people from companies engaged in the same industry. The method used is quantitative with quantitative descriptive research, using interviews, distributing questionnaires and documentation study. Multiple liner regression, coefficient of determination and simultaneous testing will be used in the analysis method. (Test - F) Fcount (174.204)> Ftable (2.70) and partially (Test - t) tcount | 3,415 | > ttable | 1.98 |, tcount | 6,191 | > ttable | 1.98 |, tcount | 4,433 | > ttable | 1.98 |. It can be concluded that motivation, communication, and work environment simultaneously and partially have a positive effect on employee performance.